Pemberdayaan Kelas Ibu Hamil Mengunakan Metode Pembelajaran Hypnoteaching - Asmalinda, Wita; Franciska, Yunetra; Shinta Yuka, Aprilia Ayu; Sumastri, Heni; Novita, Nesi (Jurnal Pengabdian kepada Masyarakat (ABDIKEMAS), 2025)
Pregnant women class (KIH) is an adult learning process (Andragogy), which is a learning activity based on learning needs. Effective learning in KIH requires class managers who are able to condition communicative and educational classes, so that KIH participants are able to follow the class well. Hypnotic conditions by exploring the subconscious are a hypnoteaching learning method. The purpose of this community partnership program is to empower pregnant women's classes using the hypnoteaching learning method. This community service activity uses training and mentoring methods with the main targets being KIH managers and KIH participants. The first training was held on September 6, 2021 and continued with mentoring activities for KIH managers on October 21, 2021. The training was held in the pregnant women's class at the Pakjo Palembang Health Center. The number of participants who took part in the activity was 30 people consisting of 10 KIh managers and 20 KIH participants. It was concluded that training and mentoring using the hypnoteaching method was able to improve the skills of pregnant women's class managers and the learning interests of pregnant women's class participants.